Use of Decommissioned Anti-Personnel Mines as Part of Developing Landmine-Alternatives - Dariusz SAPIJA; Janusz ŚLIWIŃSKI; Andrzej WOJCIECHOWSKI; Michał LUDAS; Wiesław MADEJ; Łukasz CZUBATY; Piotr KRYSIAK; Daniel STRZAŁKOWSKI (Problemy Mechatroniki)
The paper presents results of the design and research works on developing alternative devices for landmines, including anti-personal ones. The devices described, which are elements of the Controlled Explosive Charges System, were built basing on the directional anti-personal mines – MON-100, which are being taken out of service with the Polish Army. The devices are economic to produce and effective on the battlefield against hostile forces. The devices developed compliant requirements of the Ottawa Treaty and Polish Defence Standards on safety of use.